THE IMPLEMENTATION DIFFERENTIATED LEARNING IN TEACHING NARRATIVE TEXTS TO ENHANCE STUDENTS’ CRITICAL THINKING - Ahmad Muflihin; Dias Andris Susanto; AB. Prabowo K.A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In today’s educational landscape, the development of critical thinking skills is essential for equipping students to navigate complex information and real-world challenges. Conventional teaching methods, however, often fall short in fostering these skills, particularly in the context of analyzing narrative texts. Differentiated learning, a teaching strategy that tailors instruction to meet diverse student needs, has shown promise in creating a more engaging and personalized learning environment. This research aims to analyze the effectiveness of differentiated learning in enhancing students' critical thinking skills in learning narrative texts. Differentiated learning was applied to the experimental group, while the control group received conventional instruction. This study utilizes a mixed-methods approach, integrating both quantitative and qualitative data. Quantitative data was collected through pre- and post-tests in both groups and analyzed using statistical methods to measure improvements in critical thinking. The results showed a significant increase in the experimental group's scores, with a pre-test average of 55.0 and a post-test average of 83.6, marking an improvement of 28.6 points, compared to the control group’s increase from 48.3 to 64.6, or 16.3 points. Statistical analysis confirmed that this difference was significant, supporting the hypothesis that differentiated learning more effectively enhances critical thinking than conventional methods. Qualitative data, obtained through observation, interviews, and documentation, provided deeper insights into students’ experiences and perceptions of differentiated learning. Students in the experimental group felt more confident, actively engaged in discussions, and were better able to analyze narrative structures and themes. They also reported that while social media aided learning, it occasionally distracted from focus. Overall, differentiated learning proved effective in improving students' critical thinking, motivation, and reflective abilities. These findings suggest that differentiated methods can enhance the quality of learning in schools, particularly in understanding and analyzing narrative texts. This study underscores the need for innovative teaching strategies to foster critical thinking in education.